(untitled) (Research, Society and Development, 2021)
Introduction: autoimmune diseases are caused by a persistent loss of control mechanisms responsible for maintaining tolerance to self antigens. General Objective: to analyze the importance of a balanced diet for people with autoimmune disease, as well as the foods to be avoided. Methodology: To carry out this study, we opted for a research in the modality of integrative literature review. This is a research method pointed out as a tool of great relevance in the field of health, as it provides a search, critical assessment and synthesis of evidence on an investigated topic. Results and Discussion: The nutritional status is extremely important in the balance of the immune system, and the composition of the diet plays a fundamental role in maintaining the health of all individuals, including those with autoimmune diseases. Final Considerations: Through the development of this study, it can be seen that food intake is seen as an important ally in the reduction and prevention of inflammatory processes that impair the quality of life, and that may negatively affect the clinical condition of the carrier patient. of autoimmune diseases.